HIV and syphilis co-infection increasing among men who have sex with men in China: a systematic review and meta-analysis. - Eric P F Chow; David P Wilson; Lei Zhang (PLoS ONE, 2011)
Background This study aims to estimate the magnitude and changing trends of HIV, syphilis and HIV-syphilis co-infections among men who have sex with men (MSM) in China during 2003-2008 through a systematic review of published literature. Methodology/principal findings Chinese and English literatures were searched for studies reporting HIV and syphilis prevalence among MSM from 2003 to 2008. The prevalence estimates were summarized and analysed by meta-analyses. Meta-regression was used to identify the potential factors that are associated with high heterogeneities in meta-analysis. Seventy-one eligible articles were selected in this review (17 in English and 54 in Chinese). Nationally, HIV prevalence among MSM increased from 1.3% during 2003-2004 to 2.4% during 2005-2006 and to 4.7% during 2007-2008. Syphilis prevalence increased from 6.8% during 2003-2004 to 10.4% during 2005-2006 and to 13.5% during 2007-2008. HIV-syphilis co-infection increased from 1.4% during 2005-2006 to 2.7% during 2007-2008. Study locations and study period are the two major contributors of heterogeneities of both HIV and syphilis prevalence among Chinese MSM. Conclusions/significance There have been significant increases in HIV and syphilis prevalence among MSM in China. Scale-up of HIV and syphilis screening and implementation of effective public health intervention programs should target MSM to prevent further spread of HIV and syphilis infection.